Glycerol oxidation reaction using PdAu/C electrocatalysts - Ottoni, Cristiane Angélica [UNESP]; da Silva, Sirlane G.; De Souza, Rodrigo F. B.; Neto, Almir Oliveira (Springer Nature, 2016)
Glycerol oxidation reactions were evaluated using PdAu/C electrocatalysts under alkaline conditions. These electrocatalysts were synthesized in different ratios (100:0, 75:25, 50:50, 25:75, and 0:100), using the borohydride reduction method. The materials were characterized with X-ray diffraction (XRD), transmission electron microscopy (TEM), and electrochemical techniques associated by in situ attenuated total reflectance Fourier transformed infrared spectroscopy (ATR-FTIR). According to the XRD diffractograms, the presence of Pd and Au (face-centered cubic (fcc)) phases and Pd-Au (fcc) alloys were detected. Cyclic voltammetry assisted by ATR-FTIR in situ and chronoamperometry experiments revealed that the addition of Au remarkably enhances the electrocatalytic activity, due to the action of bifunctional effect, with addition of the interactions of alcohoxide with hydroxylate species in gold surface, and the stability of Pd/C catalysts. Highest current density (≈4 mA mgmetal −1) was achieved for the catalyst Pd50Au50/C and Pd75Au25/C, which is two times higher than that achieved by Pd/C (2 mA mgmetal −1), demonstrating the beneficial effect of the PdAu alloy.
Keywords: Glycerol oxidation reaction; Palladium-electrocatalyst; PdAu alloy